Combinação do uso de cama de aviário com nitrogênio em cobertura na cultura do milho - Senhor, João Paulo da Cruz (2019)
Brazil is one of the largest producers of maize and consumer of chemical fertilizers in the world. Residues of poultry can be used as an alternative to organic fertilization, as is the case with poultry litter. Thus, the objective of this work was to evaluate the use of poultry litter in combination with different levels of nitrogen and to compare with the use of recommended mineral fertilization for the crop, determining the best dose of nitrogen to be combined with the use of the poultry litter for corn performance. For this, the combinations of 0,75, 150 e 225 kg of N ha' in coverage, with 6 t ha-1 poultry litter and compared to a control treatment consisting of the recommended mineral fertilization for the crop, with 45 kg ha-1 of N, 120 kg ha-1 of P 205 e 120 kg ha' of K2O in fertilization of the hybrid 30 f 53. The grain yield, number of grains per plot, mass of one thousand grains, number of rows per spike and number of grains per row were evaluated. No significant difference was observed between the combination of N doses with 6 t ha' of poultry litter compared to the control treatment, composed of mineral fertilization. The isolated use of 6 t ha-1 of aviary poultry litter without complementation of nitrogen fertilization on cover showed the lowest yield and the worst performance for the other variables compared to the control and the combination with N levels. Regarding the performance of the doses used in combination with the poultry litter, the best performance was obtained with the complementation of 150 kg ha' of N. The response of all variables is a quadratic function where performance is impaired using very high levels. The use of poultry litter in combination with nitrogen doses can meet the nutritional needs of maize and can be used instead of mineral fertilization. The best performance of corn considering the association between fertilization with avian litter in the application of 6 t ha-') and levels of nitrogen is obtained with doses higher than 150 kg ha' and less than 250 kg hal, of the latter.